Making small enterprises more competitive through more innovative entrepreneurship development programs proceedings of the 1st Asia-Pacific Symposium on Small Enterprise and Entrepreneurship Development (SEED Symposium), Bangkok, 18-21-February 1987, Manila, 25-28 February 1987 (Technonet Asia, 1987)
"The symposium [Making Small Enterprises More Competitive Through More Innovative Entrepreneurship Development Programs] yielded a total of 53 resource papers, exclusive of addresses given during the opening and closing ceremonies. These materials represent a rich and wide source of information on experience and know-how on small enterprise and entrepreneurship development. In this volume, we have not presented the papers in chronological sequence rather, with the readers' interest in mind, grouped them into four major topics: Entrepreneurship Development, Industrial Cooperation and Technology Transfer Opportunities, Productivity and Competitiveness, and Small Enterprise and Its Environment. A synopsis is also given."--Foreword.